Blockchain-based solutions in achieving SDGs after COVID-19 - Ahmet Faruk Aysan; Fouad Bergigui; Mustafa Disli (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
In this paper, we attempt to explore the extent to which the hard won development gains over the last several years could be reversed due to the unfolding COVID-19 global pandemic, how we can reboot the global response to accelerate the SDGs in times of uncertainties, and most importantly how to turn the recovery into an opportunity to build back better and more resilient economies. To do so, we examine the case of blockchain as one of the emerging innovative work-streams in development practices that could lead the way forward and pave the path for new developmental narratives as we all navigate the uncharted territories of the new digital age. This paper provides useful insights about the underlying dynamics underpinning the adoption of blockchain backedsolutions for sustainable development, and it showcases some of the promising use-cases being developed through trial-and-error experiments by its early adopters. The paper offers a deep dive into a burgeoning development practice in search of disrupting business-as-usual to solve increasingly complex development challenges by mainstreaming innovations such as blockchainenabled solutions to rethink the ways in which development solutions are being delivered across the SDG spectrum. This work points to the significant potential of blockchain technology as a game changer in solving some of the most pressing issues hindering the global recovery post Covid-19 to transition towards greener and more inclusive economies. Nevertheless, we also stress that the hype-cycle behind the "let's blockchain it" trend does not mean that blockchain-backed solutions are necessarily superior to other alternatives which might be less costly and less technical in nature. Development practitioners prototyping and implementing blockchain-based solutions for sustainable development can utilize these insights and discussions to make informed decisions in their journey to harness the disruptive potential of blockchain alone or in tandem with other emerging technologies in the new world of business as unusual.
Keywords: O16; O19; O35; P16; Q01; Q56; 650; SDGs; Covid-19; innovation; blockchain; development